Domes and Crosses: Exploiting synergies in two methodologies for biaxial tensile testing of membrane tissues - Pons, Daniel Jonathan (Department of Mechanical Engineering, 2023)
Biaxial tensile testing is the preferred method for mechanically testing membranous tissue as it can capture the tissue load response more holistically than uniaxial methods. There are two dominant approaches within the field of biaxial tensile testing: planar and bulge. Both methods can induce a state of biaxial tension within a specimen and both have their advantages and disadvantages. Bulge testing has the benefit of imposing a simple boundary condition on the tissue, making it quick and easy to set up. Planar Biaxial Tensile (PBT) testing is very sensitive to specimen preparation and requires non-trivial gripping systems. Some knowledge of the direction of maximum stiffness, prior to specimen mounting, is necessary for PBT to yield useful data. However, literature suggests that PBT is the more rigorous of the methods when it comes to collecting data to fully characterise a material model for membrane tissues. This study used the ease of bulge testing to determine the mean fibre axis of the tissue which informed the angle of PBT specimen excision. This was a rapid, non-destructive and creative method to avoid otherwise highly expensive imaging approaches to determine mean fibre direction. Further work was also done to develop a method of accurately determining specimen thickness for very thin tissues using a creative histological technique. By using a block of cutting medium to shape the membrane during processing steps, all four of the loaded edges of the tissue could be sectioned simultaneously for thickness measurement. Finally, the study served to develop a membrane tissue test protocol for further research using the in-house built biaxial tensile machines.